(untitled) (Research, Society and Development, 2020)
Bearing in mind that the sand used as fine aggregate in the concrete manufactured in the City of Teresina comes entirely from the Poti and Parnaíba rivers, and the massara extracted from washing the material that gives rise to the pebble found in deposits. The present work aims at the mechanical characterization of the materials that make up the concrete, using the washed massará as fine aggregate, obeying the same proportions of aggregates, water and CP IV-32RS cement for conventional concrete. The particle size tests, cone trunk reduction and axial compression of cylindrical specimens were performed. After carrying out all the procedures, it was observed that the results achieved have similar compressive strength when compared to conventional concrete dosing, proving that it is possible to use the washed massará as an alternative of fine aggregate for the production of concrete.